The Influence of Social Media Marketing on E-WOM and In-tention to Join in Student Organizations - Widya Astuti; Satria Bangsawan (Digital Innovation : International Journal of Management, 2025)
This research seeks to ascertain the impact of Social Media Marketing on Electronic Word of Mouth (e- WOM) and the Intention to Become a Member of Student Activity Units (UKM) among followers of the Instagram account @radiokampusunila. The background of this research is the low participation of Universitas Lampung students in campus organizations, even though promotional strategies through social media have been actively implemented. This study combines a survey method with a quantitative associative approach through online questionnaires distributed to 121 respondents. Purposive sampling with criteria, an active students of Universitas Lampung who follow the @radiokampusunila Instagram account, is the method of sampling that is employed The variables include Social Media Marketing (X), e-WOM (Y1), also the Intention to Become a Member (Y2). With the use of SPSS, multiple linear regression analysis was performed on the data. . The findings demonstrated the positive and substantial impact of social media marketing on e-WOM, the positive and significant impact of social media marketing on the intention to join, and the positive and significant impact of e-WOM on the intention to join.